(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Misrepresentation is an element that detrimentally affects an individual’s free will and consent to enter into a contract. The legal provision relating to contractual misrepresentation used to this day in Malaysia is Section 18 of the Contracts Act 1950 (Act 136), which is applicable to all types of contracts in Malaysia. However, there are certain situations that present ambiguities which could cause confusion, especially in cases of contractual misrepresentation involving the definition, elements, categories and remedies for misrepresentation. This research applies the content analysis method in discussing the abovementioned problem by referring to decided court cases. The finding of this research is that Section 18 of the Contracts Act 1950 needs to be amended in its entirety, as there are uncertainties and matters that need clarification regarding the definition, categories and remedies for misrepresentation that have resulted in a lack of consistency and uniformity in court decisions. Keywords: categories of misrepresentation, remedies for misrepresentation, Contracts Act 1950 (Act 136), uncertainty, inconsistency in case decisions